Ground state solution for asymptotically periodic fractional p-Laplacian equation. (October 2021) - Mi, Heilong; Deng, Xiaoqing; Zhang, Wen
Abstract: In this paper, we study a class of fractional p -Laplacian equation with asymptotically periodic conditions. Under some suitable conditions we obtain two new existence results of ground state solutions by using variational methods.